Unrest at Domuyo Volcano, Argentina, Detected by Geophysical and Geodetic Data and Morphometric Analysis - Ana Astort; Thomas R. Walter; Francisco Ruiz; Lucía Sagripanti; Andrés Nacif; Gemma Acosta; Andrés Folguera (Remote Sensing, 2019)
New volcanic unrest has been detected in the Domuyo Volcanic Center (DVC), to the east of the Andes Southern Volcanic Zone in Argentina. To better understand this activity, we investigated new seismic monitoring data, gravimetric and magnetic campaign data, and interferometric synthetic aperture radar (InSAR) deformation maps, and we derived an image of the magma plumbing system and the likely source of the unrest episode. Seismic events recorded during 2017−2018 nucleate beneath the southwestern flank of the DVC. Ground deformation maps derived from InSAR processing of Sentinel-1 data exhibit an inflation area exceeding 300 km2, from 2014 to at least March 2018, which can be explained by an inflating sill model located 7 km deep. The Bouguer anomaly reveals a negative density contrast of ~35 km wavelength, which is spatially coincident with the InSAR pattern. Our 3D density modeling suggests a body approximately 4−6 km deep with a density contrast of −550 kg/m3. Therefore, the geophysical and geodetic data allow identification of the plumbing system that is subject to inflation at these shallow crustal depths. We compared the presence and dimensions of the inferred doming area to the drainage patterns of the area, which support long-established incremental uplift according to morphometric analysis. Future studies will allow us to investigate further whether the new unrest is hydrothermal or magmatic in origin.